2014
DOI: 10.1111/ppa.12211
|View full text |Cite
|
Sign up to set email alerts
|

The genetic characterization of Xanthomonas arboricola pv. juglandis, the causal agent of walnut blight in Poland

Abstract: Leaves and fruits of walnut trees exhibiting symptoms of bacterial blight were collected from six locations in Poland. Isolations on agar media resulted in 18 bacterial isolates with colony morphology resembling that of the Xanthomonas genus. PCR using X1 and X2 primers specific for Xanthomonas confirmed that all isolates belonged to this genus. In pathogenicity tests on unripe walnut fruits, all isolates caused typical black necrotic lesions covering almost the entire pericarp. Results of selected phenotypic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…Commonly used methods for designing SCAR primers include rep-PCR (repetitive PCR) (Sangdee et al 2013 ), randomly amplified polymorphic DNA (RAPD) (Liu et al 2012 ; Cheng et al 2015 ), amplified fragment length polymorphism (AFLP) (Zhang et al 2012 ), PCR with universal rice primers (URP-PCR) (Lim et al 2009 ) and inter-simple sequence repeat (ISSR) (Giaj Merlera et al 2015 ). Although the PCR MP method was described so far as helpful in the study of genetic diversity of bacteria and yeast (Leibner-Ciszak et al 2010 ; Kałużna et al 2010b , 2014 ; Zasada et al 2014 ), it has not been previously reported to be used for the selection of SCAR markers. In this work, the PCR MP is for the first time used for the design of SCAR primers specific for detection of plant pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly used methods for designing SCAR primers include rep-PCR (repetitive PCR) (Sangdee et al 2013 ), randomly amplified polymorphic DNA (RAPD) (Liu et al 2012 ; Cheng et al 2015 ), amplified fragment length polymorphism (AFLP) (Zhang et al 2012 ), PCR with universal rice primers (URP-PCR) (Lim et al 2009 ) and inter-simple sequence repeat (ISSR) (Giaj Merlera et al 2015 ). Although the PCR MP method was described so far as helpful in the study of genetic diversity of bacteria and yeast (Leibner-Ciszak et al 2010 ; Kałużna et al 2010b , 2014 ; Zasada et al 2014 ), it has not been previously reported to be used for the selection of SCAR markers. In this work, the PCR MP is for the first time used for the design of SCAR primers specific for detection of plant pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…MLSA has been shown to be useful to characterize strains of X . arboricola [ 2 , 5 , 18 , 45 , 46 ]. In this work, we utilized a MLSA scheme proposed by Young and collaborators [ 18 ], which is based in the analysis of partial sequences of the genes dnaK , fyuA , gyrB and rpoD .…”
Section: Discussionmentioning
confidence: 99%
“…The evolutionary rate of change within microsatellites is considerably higher than most other types of DNA; thus, the likelihood of polymorphism in these sequences is greater in comparison with other molecular markers (Schl€ otterer, 2000). In the PCR MP assay, the restriction patterns are a representation of the whole genome and are dependent upon the enzyme cleavage sequences and the melting temperature of the amplified restriction products (Kału_ zna et al, 2014). In contrast, in the RAPD assay, the arbitrary primers, although designed to amplify repetitive sequences, aligned more randomly to the genome (Wilson & Sharp, 2006).…”
Section: Discussionmentioning
confidence: 99%